(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Obesity has transitioned from a localized concern of affluence to a pervasive global pandemic. Characterized by a Body Mass Index (BMI) ≥ 30 kg/m², it acts as a primary catalyst for Type 2 Diabetes, Cardiovascular Diseases, and various malignancies. This 10-page review explores the evolution of the obesity crisis, the biological mechanisms of adipose tissue dysfunction, and the shifts in treatment including the 2025-2026 breakthrough in GLP-1 and GIP dual-agonist therapies.